Annals of the Institute of Statistical Mathematics - Tsubaki, Hiroe; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer.)
Annals of the Institute of Statistical Mathematics (AISM) aims to provide a forum for open communication among statisticians, and to contribute to the advancement of statistics as a science to enable humans to handle information in order to cope with uncertainties. It publishes high-quality papers that shed new light on the theoretical, computational and/or methodological aspects of statistical science. Emphasis is placed on (a) development of new methodologies motivated by real data, (b) development of unifying theories, and (c) analysis and improvement of existing methodologies and theories.
Keywords: Statistics; Statistics, general; Statistics for Business, Management, Economics, Finance, Insurance